ANALISIS FAKTOR PERBEDAAN HASIL BELAJAR KELAS XI IPS PELAJARAN EKONOMI SMA ASISI PONTIANAK - Utami, Hana Syarifah; Halidjah, Siti; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIn learning to write poetry in class V Public Elementary School 66 Pontianakthere are still many students who have not been able to write poetry well. This needs to be overcome by updating learning, either through the use of media or learning models. One that has been tested and proven to support students' skills in writing poetry is to apply an outdoor learning model. Based on the analysis of the situation, the problem in this study is "How is the influence of the application of outdoor learning models on poetry writing skills of fifth grade students of Public Elementary School 66 Pontianak?".This study aims to analyze the effect of the application of outdoor learning models on poetry writing skills.The method used is the experimental method, while the form of research used pre-experimental design with the design of the group-pretest-posttest design. The population and sample in this study were all fifth grade students of Public Elementary School 66 Pontianakin the academic year 2017/2018 totaling 36 students. Data collection techniques used in this study are direct observation techniques and measurement techniques. Based on the results of data analysis of the mean value of pre-test 72.19 and post-test mean 77.53. The result of the t test is obtained by t table = 5%, with db = 35 is 2.03. Because t count (4.68)> t table (2.03), then the alternative hypothesis (Ha) is accepted. So that it can be concluded that there is an effect of applying the outdoor learning model to the poetry writing skills of fifth grade students of Public Elementary School 66 Pontianak. Keywords: Influence, Outdoor Learning Models, Poetry Writing Skills